Growth of the Stabilized HeLa Cell line in Chromium-Cobalt Extract of Surface - Layered Titanium Nitride and Zirconium Nitride - P. Prachár; J. Vaněk; S. Bartáková; V. Březina (Czech Dental Chamber, 2005)
The materials used recently in dental implantology are exclusively made of titanium alloy. This is reflected in a difficult processing of the material.Preparation and economic point of view are also very demanding. Our aim was to find a material with high physicomechanical and biological properties. Our selection was an alloy of chromium and cobalt that exhibited better physical properties than titanium alloy. Biological properties were maintained by a layering of titanium nitride and zirconium nitride on the cromium-cobalt alloy. The material with surface - layered structure was biologically tested. The first test was a cell growth test. The study is a part of the project No. 7356-3 provided by IGA grant of the Czech Ministry of Health.